Breaking with convention in Italian art - Fischer, Julia C. (Cambridge Scholars Publishing, 2017)
This volume explores the various ways in which artists, patrons, and art historians throughout history have broken bad by defying authority, challenging convention, or rejecting the norm. For example, artists also sometimes break away from tradition by using unconventional iconography, as is the case in Chapter Two, which investigates how Etruscan tomb reliefs show mourning rather than celebration. The book also includes a chapter in which an art historian breaks bad by challenging the conventional interpretation and date of an object, thus eschewing tradition and defying authority. In this case, Chapter Three disputes the largely accepted Hellenistic date and interpretation of the Tazza Farnese, and instead asserts that the cameo must be Roman. 00Spanning the art of ancient Etruria to the twentieth century, the eight chapters here explore the theme of breaking bad from a variety of time periods and artistic media, from Etruscan mirrors and Roman cameos to Baroque portraits and Italian Pop Art. Scholars approach the topic of breaking bad from a number of perspectives, including examining the artist, patronage, reception, propaganda, iconography, methodology, and use
Based on papers from the 2016 Southeastern College Art Conference
Keywords: Kunst; Italien; Art, Italian / Congresses; Konferenzschrift -- 2016 -- Birmingham, Ala.